Species delimitation and phylogenetic relationships in the genus Trypoxylon (Hymenoptera: Crabronidae) using molecular markers: an alternative to taxonomic impediment. Issue 4 (18th May 2020) - Sabadini, Camila Pereira; Machado, Carolina Barros; Vilhena, Patrícia Dos Santos; Garófalo, Carlos Alberto; Del Lama, Marco Antonio
Abstract : The taxonomic identification of species is an essential issue in biological studies, as the uncertain taxonomy of a species hinders the investigation of its biology. Limitations regarding the description and identification of new species characterizes the "taxonomic impediment". The genus Trypoxylon is an example of a taxon with this difficulty, particularly in the Neotropical region. It is a diverse genus composed of 631 described species that is divided in two subgenera – Trypoxylon ( Trypoxylon ), and Trypoxylon ( Trypargilum ), which are subdivided into groups and species complexes. To overcome the taxonomic impediment of Trypoxylon, the aim of the present study is to i) estimate molecular variation in order to delimit Trypoxylon species, and ii) determine evolutionary relationships among species to validate the morphological and behaviour-based infrageneric classification employing molecular data. The species delimitation analysis based on 333 COI sequences using genetic distance and phylogenetic and coalescence methods enabled us to define the single-threshold GMYC as the best model, as 45 out of 40 morphotypes/species were defined using this method. To determine phylogenetic relationships, we used sequences from two mitochondrial markers COI (n = 38) and CytB (n = 38) and a nuclear marker pol (n = 26), showing that molecular data were congruent with the infrageneric division of Trypoxylon and pointing to a probable third clade among Trypoxylon ( Trypargilum ) species. Moreover, the COI sequence-based estimation of divergence time (n = 102) suggests that Trypoxylon diversified in the Upper Cretaceous, and subsequent cladogenetic events occurred more frequently between the Eocene/Oligocene and throughout the Neogene. In summary, the molecular approach proved to be useful for overcoming difficulties in identifying Neotropical species of Trypoxylon .